2018
DOI: 10.1177/1368430218769744
|View full text |Cite
|
Sign up to set email alerts
|

When we want them to fear us: The motivation to influence outgroup emotions in collective action

Abstract: Prior work has shown that the experience of group-based emotions can motivate disadvantaged group members to engage in collective action. In the current research, we tested whether such action can also be driven by the motivation to induce certain emotions among the outgroup to the extent that disadvantaged group members believe this would help them attain their social change goals. We tested this hypothesis in three studies (two correlational and one experimental) within the context of the Israeli–Palestinian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Finally, the two regulation processes we mentioned so far, of emotional disengagement and social category reappraisal, relate to individuals' attempt to regulate or control their own emotional experiences. However, people often regulate the emotions of others and have their emotions regulated by others, both in the interpersonal context and in the intergroup context (Campos, Campos, & Barrett, ; Gross & Thompson, ; Hasan‐Aslih et al, Under review; Lakey & Orehek, ; Netzer, Halperin, & Tamir, Under review; Netzer, Van Kleef, & Tamir, ). This type of interpersonal or intergroup emotion regulation usually entails subjecting the others to pleasant or unpleasant stimuli in order to evoke the wanted emotion.…”
Section: Ggs and Intergroup Emotionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the two regulation processes we mentioned so far, of emotional disengagement and social category reappraisal, relate to individuals' attempt to regulate or control their own emotional experiences. However, people often regulate the emotions of others and have their emotions regulated by others, both in the interpersonal context and in the intergroup context (Campos, Campos, & Barrett, ; Gross & Thompson, ; Hasan‐Aslih et al, Under review; Lakey & Orehek, ; Netzer, Halperin, & Tamir, Under review; Netzer, Van Kleef, & Tamir, ). This type of interpersonal or intergroup emotion regulation usually entails subjecting the others to pleasant or unpleasant stimuli in order to evoke the wanted emotion.…”
Section: Ggs and Intergroup Emotionsmentioning
confidence: 99%
“…This study also found that participants' motivation to regulate their counterparts' emotions affected the participants' behavior through the mediation of the belief in the instrumentality of emotions. Although the motivations to regulate out‐group's emotions have been mapped out by existing research (Hasan‐Aslih et al, Under review; Netzer et al, ; Netzer et al, Under review), the actual ability and efficiency of regulating an out‐group's emotions in the context of intergroup context remain unexamined. Indeed, as a result of physical and psychological barriers that are inherent in intractable intergroup conflict (Bar‐Tal & Halperin, ), the ability to directly and intentionally affect the out‐group in any way, including in terms of emotion regulation, might prove challenging (as can be seen in the different endeavors to promote intergroup communication that often turn awry, Hameiri, Bar‐Tal, & Halperin, ).…”
Section: Ggs and Intergroup Emotionsmentioning
confidence: 99%
“…Therefore, it stands to reason that disadvantaged group members who seek hope in the face of setbacks, particularly those who have group efficacy beliefs, will be motivated to engage in collective action because it is congruent with their desire for hope. Consistent with this, the emotional preferences literature suggests that the implications of motivations to feel certain emotions go beyond experiencing these emotions, with several works indicating that emotional motivations affect behavioral tendencies such as collective action intentions (Hasan-Aslih, Netzer, et al, 2019; Porat et al, 2016). We thus aim to investigate whether the motivation to feel hope for social change, when combined with group efficacy beliefs, predicts willingness to partake in collective action.…”
Section: Does Motivation For Hope Predict Collective Action When Paired With Efficacy?mentioning
confidence: 72%
“…Future research could benefit from examining what strategies, if any, people low in efficacy use to bridge such gaps as well as the implications these have for their well-being. Finally, previous research on hope among disadvantaged group members differentiated between hope that is equality oriented and hope that is oriented toward harmony between groups (Hasan-Aslih, Pliskin, et al, 2019). In future research, it would be interesting to explore and compare motivated hope for equality and motivated hope for harmony as well as their relationship with collective action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation